2023
DOI: 10.1097/corr.0000000000002625
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Are Associated With Early Career Attrition Among Orthopaedic Surgeons in the United States?

Abstract: Background The attrition of medical personnel in the United States healthcare system has been an ongoing concern among physicians and policymakers alike. Prior studies have shown that reasons for leaving clinical practice vary widely and may range from professional dissatisfaction or disability to the pursuit of alternative career opportunities. Whereas attrition among older personnel has often been understood as a natural phenomenon, attrition among early-career surgeons may pose a host of additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…I think it is important to specifically address the conclusion in the current study [2] that early career attrition occurs more frequently in women than in men. This is an important finding and should be used to draw attention to the challenges that women face in practice.…”
Section: How Do We Get There?mentioning
confidence: 94%
See 4 more Smart Citations
“…I think it is important to specifically address the conclusion in the current study [2] that early career attrition occurs more frequently in women than in men. This is an important finding and should be used to draw attention to the challenges that women face in practice.…”
Section: How Do We Get There?mentioning
confidence: 94%
“…Prior studies have shown that the reasons for leaving practice vary widely and involve personal and professional factors including issues related to burnout, compensation, the burden of bureaucratic tasks, and the challenge of work-life balance [1, 3, 6]. There are also reasons for attrition like injury, illness, and disability that are not “voluntary.” Although we do not know how many this would apply to in this study of 78 people [2], it is reasonable to postulate that it would be a small number. Therefore, our efforts must be directed toward understanding the reasons for voluntary early career attrition.…”
Section: Where Do We Need To Go?mentioning
confidence: 97%
See 3 more Smart Citations